Pharmacotherapy handbook - Wells, Barbara G.;Dipiro, Joseph T.;Schwinghammer, Terry L.;Dipiro, Cecily V. (New York : McGraw Hill Education, 2012)
This book provides practitioners and students with the information necessary to support drug therapy decision making for more than 140 diseases and disorders.
SECTION 1 BONE AND JOINT DISORDERS / Terry L. Schwinghammer -- 1. Gout and Hyperuricemia -- 2. Osteoarthritis -- 3. Osteoporosis -- 4. Rheumatoid Arthritis -- SECTION 2 CARDIOVASCULAR DISORDERS / Terry L. Schwinghammer -- 5. Acute Coronary Syndromes -- 6. Arrhythmias -- 7. Cardiac Arrest -- 8. Dyslipidemia -- 9. Heart Failure -- 10. Hypertension -- 11. Ischemic Heart Disease -- 12. Shock -- 13. Stroke -- 14. Venous Thromboembolism -- SECTION 3 DERMATOLOGIC DISORDERS / Terry L. Schwinghammer -- 15. Acne Vulgaris -- 16. Dermatologic Drug Reactions and Common Skin Condition -- 17. Psoriasis -- SECTION 4 ENDOCRINOLOGIC DISORDERS / Terry L. Schwinghammer -- 18. Adrenal Gland Disorders -- 19. Diabetes Mellitus -- 20. Thyroid Disorders -- SECTION 5 GASTROINTESTINAL DISORDERS / Terry L. Schwinghammer -- 21. Cirrhosis and Portal Hypertension -- 22. Constipation -- 23. Diarrhea -- 24. Gastroesophageal Reflux Disease -- 25. Hepatitis, Viral -- 26. Inflammatory Bowel Disease. Contents note continued: 27. Nausea and Vomiting -- 28. Pancreatitis -- 29. Peptic Ulcer Disease SECTION 6 GYNECOLOGIC AND OBSTETRIC DISORDERS / Barbara G. Wells -- 30. Contraception -- 31. Menopause & Perimenopausal & Postmenopausal Hormone Therapy -- 32. Pregnancy and Lactation: Therapeutic Considerations -- SECTION 7 HEMATOLOGIC DISORDERS / Cecily V. DiPiro -- 33. Anemias -- 34. Sickle Cell Disease -- SECTION 8 INFECTIOUS DISEASES / Joseph T. DiPiro -- 35. Antimicrobial Regimen Selection -- 36. Central Nervous System Infections -- 37. Endocarditis -- 38. Fungal Infections, Invasive -- 39. Gastrointestinal Infections -- 40. Human Immunodeficiency Virus Infection -- 41. Influenza -- 42. Intraabdominal Infections -- 43. Respiratory Tract Infections, Lower -- 44. Respiratory Tract Infections, Upper -- 45. Sepsis and Septic Shock -- 46. Sexually Transmitted Diseases -- 47. Skin and Soft-Tissue Infections -- 48. Surgical Prophylaxis -- 49. Tuberculosis -- 50. Urinary Tract Infections and Prostatitis. Contents note continued: -- 51. Vaccines, Toxoids, and Other Immunobiologics -- SECTION 10 NEUROLOGIC DISORDERS / Barbara G. Wells -- 52. Alzheimer's Disease -- 53. Epilepsy -- 54. Headache: Migraine and Tension-Type -- 55. Pain Management -- 56. Parkinson's Disease -- 57. Status Epilepticus -- SECTION 10 NUTRITIONAL DISORDERS / Cecily V. DiPiro -- 58. Assessment of Nutrition Status and Nutrition Requirements -- 59. Enteral Nutrition -- 60. Obesity -- 61. Parenteral Nutrition -- SECTION 11 ONCOLOGIC DISORDERS / Cecily V. DiPiro -- 62. Breast Cancer -- 63. Colorectal Cancer -- 64. Lung Cancer -- 65. Lymphomas -- 66. Prostate Cancer -- 67. Renal Cell Carcinoma -- SECTION 12 OPHTHALMIC DISORDERS / Cecily V. DiPiro -- 68. Glaucoma -- SECTION 13 PSYCHIATRIC DISORDERS / Barbara G. Wells -- 69. Anxiety Disorders -- 70. Bipolar Disorder -- 71. Major Depressive Disorder -- 72. Schizophrenia -- 73. Sleep Disorders -- 74. Substance-Related Disorders -- SECTION 14 RENAL DISORDERS / Cecily V. DiPiro. Contents note continued: 75. Acid-Base Disorders -- 76. Acute Kidney Injury -- 77. Chronic Kidney Disease -- 78. Drug Therapy Individualization for Patients with Chronic Kidney Disease -- 79. Electrolyte Homeostasis -- SECTION 15 RESPIRATORY DISORDERS / Terry L. Schwinghammer -- 80. Allergic Rhinitis -- 81. Asthma -- 82. Chronic Obstructive Pulmonary Disease -- SECTION 16 UROLOGIC DISORDERS / Cecily V. DiPiro -- 83. Benign Prostatic Hyperplasia -- 84. Erectile Dysfunction -- 85. Urinary Incontinence -- APPENDICES / Barbara G. Wells -- Appendix 1 Allergic and Pseudoallergic Drug Reactions -- Appendix 2 Geriatrics -- Appendix 3 Drug-Induced Hematologic Disorders -- Appendix 4 Drug-Induced Liver Disease -- Appendix 5 Drug-Induced Pulmonary Disease -- Appendix 6 Drug-Induced Kidney Disease.
Includes index.
Keywords: DRUG THERAPHY